SOFTWARE APPLICATIONS FOR TEACHING ENGLISH IN THE JUNIOR LEVEL EDUCATION IN CLARA (CEC) - Arnithia Khristiyantie; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2006)
Clara Education Center (CEC), is an institution that provides guidance in several areas of education, one of them is English.  Junior One level is followed by children aged 5-6 years or before entry into primary school (SD).  In the process of teaching, teachers using tape, cassette, book stories and songs. Obstacles arise in the process of teaching in terms of efficiency and effectiveness of time and ease of use of facilities, so that created an application software for teaching to overcome these constraints. In the application software are included on the menu phonic Reader, Stories and Songs. Phonic Reader menu in which there is a submenu can be selected according to the class will learn. Stories and Songs in the menu in it there is a list of stories and songs to choose from, along with animation and music. The application software has been designed using the software Macromedia Flash MX 2004 is based on multimedia. We make this application software as a tool in teaching it will ease the process of teaching in class and will interest students in learning.